9000141910 Parte: ADada la función \(h\), halla \(\lim _{x\to -\infty }h(x)\). \[ h(x)=\begin{cases} -\frac1{x-1} & \text{si } x< 1,\\ -(x-1)^2+2 & \text{si } x\geq 1 \end{cases} \]\(0\)\(2\)\(\infty \)\(-\infty \)no existe
9000141905 Parte: ADada la función \(g\), halla \(\lim _{x\to 1}g(x)\). \[ g(x)=\begin{cases} -\frac12(x-1)^2+2 & \text{si } x < 1,\\ \frac2{x^2}+1 & \text{si } x \geq 1 \end{cases} \]no existe\(3\)\(2\)\(1\)
9000141906 Parte: ADada la función \(g\), halla \(\lim _{x\to \infty }g(x)\). \[ g(x)=\begin{cases} -\frac12(x-1)^2+2 & \text{si } x < 1,\\ \frac2{x^2}+1 & \text{si } x \geq 1 \end{cases} \]\(1\)\(0\)\(\infty \)\(-\infty \)no existe
9000141907 Parte: ADada la función \(h\), halla \(\lim _{x\to 1^{-}}h(x)\). \[ h(x)=\begin{cases} -\frac1{x-1} & \text{si } x< 1,\\ -(x-1)^2+2 & \text{si } x\geq 1 \end{cases} \]\(\infty \)\(1\)\(2\)\(-\infty \)no existe
9000062404 Parte: AResuelve el siguiente límite: \[ \lim _{x\to +\infty } \frac{x^{3} - x + 1} {1 - x^{2} - x^{3}} \]\(- 1\)\(0.5\)\(- 0.5\)\(1\)
9000062405 Parte: AResuelve el siguiente límite lateral: \[ \lim _{x\to 6^{-}}\frac{3x + 2} {x - 6} \]\(-\infty \)\(1\)\(+\infty \)\(0\)
9000062403 Parte: AResuelve el siguiente límite: \[ \lim _{x\to -1}\frac{x^{2} - 3x - 4} {x^{2} + 6x + 5} \]\(-\frac{5} {4}\)\(\frac{4} {5}\)\(\frac{5} {4}\)\(-\frac{4} {5}\)